(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
A new technology was elaborated, combining a geoinformation system (GIS) and GIS- oriented algorithmic methods of artificial intellect (AI). Numerous thematic layers for geosciences, obtained from Russian and international scientific sources, were imported into the GIS. Technology and software for integration of AI methods within the GIS in the form of the Centralized Catalogue of Geodata Processing Algorithms (CCGPA) was developed. A GIS visualization subsystem was created to provide interaction between the GIS and its users. It performs geodata layers visualization, map operations, geodata set management, execution of CCGPA-stored algorithms and representation of application results.